Estimating relative risk of within-lake aquatic plant invasion using combined measures of recreational boater movement and habitat suitability - Wittmann,Marion E; Kendall,Bruce E; Jerde,Christopher L; Anderson,Lars W. J. (PeerJ PrePrints, 2014)
Effective monitoring, prevention and impact mitigation of nonindigenous aquatic species (NAS) relies upon the ability to predict dispersal pathways and receiving habitats with the greatest risk of establishment. To examine mechanisms affecting species establishment within a large lake, we combined observations of recreational boater movements with empirical measurements of habitat suitability represented by nearshore wave energy to assess the relative risk (RR) of Eurasian watermilfoil (Myriophyllum spicatum) establishment. The model was evaluated using information from a 17 year (1995-2012) sequence of M. spicatum presence and absence monitoring. M. spicatum presence was not specifically correlated with recreational boater movements; however its establishment appears to be limited by wave action in Lake Tahoe. Of the sites in the "High" risk category (n=37), 54% had current or historical infestations, which included 8 of the 10 sites with the highest RR. Of the 11 sites in the "Medium" risk category, 5 had current or historical M. spicatum populations. Most (76%) of the sites in the "Low" risk category were observed in locations with higher wave action. Four sites that received zero boater visits from infested locations were occupied by M. spicatum. This suggests that the boater survey either represents incomplete coverage of boater movement, or other processes, such as the movement of propagules by surface currents or introductions from external sources are important to the establishment of this species. This study showed the combination of habitat specific and dispersal data in a relative risk framework can potentially reduce uncertainty in estimates of invasion risk.
Keywords: dispersal; invasive species; Eurasian milfoil; risk assessment; wave action; suitable habitat